Influence of haematocrit on international normalised ratio (INR) differences between a whole blood point-of-care coagulation monitor and reference prothrombin time in plasma - van den Besselaar, Anton M. H. P.; Witteveen, Evelina; van der Meer, Felix J. M. (Thrombosis and Haemostasis, 2008)
The CoaguChek S system is designed for use in patient self-testing. In this system a whole blood sample without sodium citrate is applied to a test strip containing thromboplastin and iron oxide particles. The detection principle is based on fibrin formation which inhibits and finally stops the movement of the iron oxide particles.In the classic prothrombin time (PT) test,ci-trate plasma is mixed with thromboplastin and an excess of calcium ions. In the monitoring of vitamin K-antagonist (VKA) treatment, all results are expressed on a common scale, i.e. international normalised ratio (INR). In patients on long-term VKA treatment, INRs were determined by the CoaguChek S system and reference methods for the classic PT. Four different CoaguChek S strip lots were evaluated.The difference in INR between the reference PT and the CoaguChek S system was negatively correlated to the haematocrit of the patients. We conclude that INR differences between CoaguChek S and plasma PT may be explained in part by the haematocrit.The magnitude of the effect of haematocrit,within the reference interval of 0.37 - 0.51,on the INR difference was not greater than approximately 10% for the combined data of the four strip lots.A bias of less than 10% seems to be acceptable clinically.
Keywords: Oral anticoagulant; prothrombin time; International Normalized Ratio; point-of-care testing; haematocrit